Synthesis and Evaluation of Antimicrobial Activities of Novel N-Substituted Indole Derivatives - Tanveer MahamadAlli Shaikh; Habtamu Debebe (Journal of Chemistry)
Indole motifs are one of the most significant scaffolds in the discovery of new drugs. We have described a synthesis of new N-substituted indole derivatives (1-3), and their in vitro antimicrobial activities were investigated. The synthesis of titled compounds has been demonstrated by utilizing commercially available starting materials. The antibacterial and antifungal activities were performed using new strains of bacteria Staphylococcus aureus, Escherichia coli, and Candida albicans using the disc diffusion method. Notably, the compound 4-(1-(2-(1H-indol-1-yl) ethoxy) pentyl)-N,N-dimethyl aniline (1) was found to be most potent than the other analogues (2 and 3), which has shown higher inhibition than the standard drug chloramphenicol.